A conjuring of light eaudiobook A novel. - Schwab, V. E. (Shades of Magic, 2017)
Londons fall and kingdoms rise while darkness sweeps the Maresh Empire, and the fraught balance of magic blossoms into dangerous territory while heroes struggle. The direct sequel to A Gathering of Shadows , and the final audiobook in the Shades of Magic epic fantasy series, A Conjuring of Light sees the newly minted New York Times bestselling author V. E. Schwab reach a thrilling conclusion concerning the fate of beloved protagonists—and old foes. Shades of Magic series 1. A Darker Shade of Magic 2. A Gathering of Shadows 3. A Conjuring of Light